PENGUATAN KOMPETENSI BERKARYA MONTASE DAN KOLASE UNTUK GURU SEKOLAH DASAR - Deni Setiawan; Yuli Witanto; Ni Kadek Aris Rahmadani; R. Agustinus Arum Eka Nugroho; Marjuni Marjuni; Isa Ansori (LPPM Universitas Bina Bangsa, 2023)
The teacher's ability and skills to create and evaluate collage and montage works of art need to follow the standards for assessing works of art. It is due to misconceptions the educational background of class teachers is not in the fine arts field, and the experience of art evaluation still needs to be improved. This service aims to improve the understanding of art and skills in creating and evaluating the art of montage and collage. The material provided is the skills to appropriately create and evaluate collages and montages. The method used is direct and guided learning. Direct learning is carried out using the teacher's conditioning method as participants take part in skill training and evaluation of the art of montage and collage. The service team acts as a resource person who directly supervises and guides. This community service activity increased their ability to create collages and montage works of art, including distinguishing and evaluating them